Biochemical Analysis Of Some Dried Sis Fishes Of The River Padma In Rajshahi (Journal of Life and Earth Science, 2012)
Seven different species viz. Chanda baculis, Chanda ranga, Amblypharyngodon mola, Oxygaster bacaila, Clupisoma atherinoides, Corica soborna, Mystus vittatus and a group of mixed SIS fishes viz. Mastacembelus pancalus, Xenntodon cancila, Chanda baculis and Glossogobius giuris were used for preparation of dust which can be preserved for a time period. The fishes were sun dried or oven dried, which are also method of preservation. Quality of the oven-dried fish was better than that of the sun-dried fish, but sun-drying process is easy and can be used in large scale. The fish powder remained in good condition for 7-9 months at normal room temperature, but at -18°C the powder was in good condition throughout the year. Highest quantity of powder from 1 kg of fish was obtained in case of the mixed species as 24.61% and the lowest in O. bacaila which was 20.52%. Biochemical analysis showed that the maximum calcium content was found as 1.34% in M. vittatus and minimum was 0.80% in mixed SIS fishes. Maximum phosphorus content was 2.90% in C. ranga and minimum was 1.72% in C. soborna. Maximum iron content was found as 45.20 mg/100g in mixed SIS fishes and minimum was found as 16.85 mg/100g in O. bacaila. The maximum moisture content was found in C. ranga (13.50%) and the minimum in mixed SIS fishes (11.65%). The maximum protein content was recorded in the mixed SIS fishes (72.45%) and the minimum in C. ranga (52.65%). The experiment was replicated three times and conducted from July 2005 to July 2008. DOI: http://dx.doi.org/10.3329/jles.v6i0.9719 JLES 2011 6: 39-43